2006
DOI: 10.3136/fstr.12.213
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Components of the Floury and Sugary Mutant Rice Cultivars Developed in the Hokuriku Region

Abstract: This paper describes the features of new characteristic rice cultivars developed in the Hokuriku region, especially Hokuriku +00 (floury mutant rice) and Hokuriku +03 (sugary mutant rice), in comparison with Koshihikari. Using Hokuriku +00, it is easy to make fine rice flour because the starch granules for this cultivar are globular and small. Therefore, this cultivar is popular because it is easy to handle. Hokuriku +03 has a high proportion of bran and high g-aminobutyric acid (GABA) content. The fineness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Identification of rice endosperm mutants could be used for breeding new rice variety with unique starch property, and could extend their applications in food industry. For example, a mutant with loosely packed round starch with relatively smaller grain was expected to generate fine rice flour with lower damaged starch content , so GM645 could be useful to produce fine flour with wider applications. Nonwaxy rice with white and opaque (chalky) tissue at the center of the kernel is regarded as brewers' rice in Japan, which is used for the brewing of rice wine (sake) .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of rice endosperm mutants could be used for breeding new rice variety with unique starch property, and could extend their applications in food industry. For example, a mutant with loosely packed round starch with relatively smaller grain was expected to generate fine rice flour with lower damaged starch content , so GM645 could be useful to produce fine flour with wider applications. Nonwaxy rice with white and opaque (chalky) tissue at the center of the kernel is regarded as brewers' rice in Japan, which is used for the brewing of rice wine (sake) .…”
Section: Discussionmentioning
confidence: 99%
“…In both jet-and pin-milling, the rice flour of six floury mutants showed significantly lower starch damage than Koshihikari 4 . Homma et al 7 also demonstrated that 'Hokuriku166', which derived from 'Kenkei2047 ( flo-1)' 10 , became finer and less damaged flour than 'Koshihikari'. The friable grain structure of floury mutant rice would lead to lower damage to endosperm starch.…”
Section: Flour Properties 1 Starch Damagementioning
confidence: 99%
“…The flo2 mutant is thus expected to be suitable for utilization as rice flour. It was shown that fine and less damaged rice flour could be obtained from flo1 ( flo4) rice 7 , while the processing properties of flo3 and flo5 mutants have not been reported. Regardless of mutant genes, the endosperm structure of floury rice mutants, which has numerous air spaces between starch granules, could make them suitable for flour processing.…”
Section: Effects Of Floury Mutant Genes On Processing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Grains with a large opaque portion in endosperm, such as milky-white and large white-core, are generally called "floury" (Satoh and Omura, 1981). Floury grains were expected to release starch granules easily and be suitable for the production of fine flour (Homma et al, 2007); however, the effect of chalkiness on grain and flour properties were not clarified because samples with different genetic backgrounds were used.…”
Section: Introductionmentioning
confidence: 99%